Genome-wide profiling of PRC1 and PRC2 Polycomb chromatin binding in Drosophila melanogaster. - Tolhuis, B.; de Wit, E.; Muijrers, I.; Teunissen, H.; Talhout, W.; van Steensel, B.; van Lohuizen, M. (Nature Genetics, 2006)
Polycomb group (PcG) proteins maintain transcriptional repression of developmentally important genes and have been implicated in cell proliferation and stem cell self-renewal. We used a genome-wide approach to map binding patterns of PcG proteins (Pc, esc and Sce) in Drosophila melanogaster Kc cells. We found that Pc associates with large genomic regions of up to approximately 150 kb in size, hereafter referred to as 'Pc domains'. Sce and esc accompany Pc in most of these domains. PcG-bound chromatin is trimethylated at histone H3 Lys27 and is generally transcriptionally silent. Furthermore, PcG proteins preferentially bind to developmental genes. Many of these encode transcriptional regulators and key components of signal transduction pathways, including Wingless, Hedgehog, Notch and Delta. We also identify several new putative functions of PcG proteins, such as in steroid hormone biosynthesis. These results highlight the extensive involvement of PcG proteins in the coordination of development through the formation of large repressive chromatin domains.